Church Rock uranium mine disaster - Knutson, Julie (21st century skills library., 2021)
Chronicles the events leading up to, during, and after the Church Rock uranium mine disaster. Includes color photographs, sidebars, a timeline, an activity, a glossary, and additional resources.